The Paradox of Openness Transparency and Participation in Nordic Cultures of Consensus - Götz, Norbert; Marklund, Carl (International Studies in Sociology and Social Anthropology, 2015)
Openness implies bottom-up empowerment and top-down transparency. The Paradox of Openness analyses the tensions encountered when openness is applied to the quest for democracy and markets, freedom and truth, compliance and transparency, and consensus and dissent in progressive Nordic societies.; Readership: All interested in the history and contemporary practices of openness and transparency, and anyone concerned with the Nordic experience of combining the call for openness with consensual political cultures.